Business economics - 415743 Dransfield, Rob (New York : Routledge, 2013)
The fundamental economic problems -- Demand -- Supply -- Markets -- Market analysis : shares, currency, and labour markets -- Market failures and imperfections -- Costs and revenues -- Analysing market structure -- Macroeconomics -- Macroeconomic issues -- international business and trade -- Current economic issues.